Recapitulation of Lecturer’s Attendance Using Android-Based Fingerprint At Dipa Makassar University - Salman, Salman; Amirah, Amirah (CogITo Smart Journal, 2025)
An academic information system is expected to provide information to lecturers, students, and administrators. There are several parts included in the academic information system, including lecturer teaching schedules, lecturer attendance systems (monitoring), and student lecture schedules. These three things are related to the results of the recapitulation of lecturer attendance for reporting on the academic section institution. Dipa Makassar University, the process of recapitulating lecturer attendance still uses a manual system, namely, officers record lecturer attendance at each session and then input it into the Excel application. This process is inefficient because the work is repetitive and time-consuming. When lecturers are delayed, there is no information provided to students, causing them to wait for long periods. In this study, the researcher developed an Android-based fingerprint application for recapitulating lecturer attendance and tardiness. The testing method applied to evaluate the application is the Black Box testing method. Based on the overall testing results, it can be concluded that the application functions properly in accordance with the system requirements and is free from errors. The testing focused on the application's input, process, and output features without examining the internal structure of the program. All tested features produced valid results and met the expected outcomes. With the presence of this application, both lecturers and students can access class schedules at any time through the Android platform. Additionally, the application provides notifications to students in case the lecturer arrives late, which significantly improves communication between lecturers and students.